Visualization and documentation of capsule and melanin production in Cryptococcus neoformans - Nichols, Connie B. (Curr Protoc, 2021)
Cryptococcus neoformans is an opportunistic fungal pathogen primarily targeting immunosuppressed populations in both resource-rich and resource-limited nations. Successful treatment is limited to a few antifungals that have become compromised by cryptococcal resistance leading to intensive research for new drug candidates. Two distinguishing hallmarks of this species are the ability to develop a polysaccharide capsule and melanization of the fungal cells. These also act as virulence factors, protecting this pathogen in the host as well as in the environment. Here we describe two classic methods to document capsule and melanin. Although initially described and documented over several decades ago, these methods remain relevant in spite of more sophisticated methodology due in part to their simplicity and cost efficiency.